Emission characteristics of gas discharge plasma on mixtures of cadmium diodide vapor, helium and xenon - Malinina, A.A.; Malinіn, A.N. (Вопросы атомной науки и техники, 2020)
The results of studying the spectral, integral, and resource characteristics of gas-discharge plasma radiation on multicomponent mixtures (cadmium diiodide with helium and xenon atoms) are presented. The creation of a gasdischarge plasma and the excitation of the components of the working mixture were carried out by a pulse-periodic (pulse repetition rate of 18…20 kHz, pulse duration ~ 150 ns) barrier discharge. Radiation in the visible spectrum of exciplex molecules of cadmium monoiodide, cadmium atoms, xenon was detected. The regularities in changes in the emission characteristics of the plasma are established depending on the repetition rate of the pump pulses, the component and quantitative composition of the mixtures. Research data is of interest for creating a gas-discharge source that radiates simultaneously in the violet, green, red, and infrared spectral ranges. Наведено результати дослідження спектральних, інтегральних і ресурсних характеристик випромінювання газорозрядної плазми на багатокомпонентних сумішах (дийодид кадмію з гелієм і малими добавками ксенону). Створення газорозрядної плазми і збудження компонент робочої суміші здійснювалося імпульсно-періодичним (частота слідування імпульсів 18…20 кГц, тривалість імпульсів ~ 150 нс) бар’єрним розрядом. Виявлено випромінювання у видимій області спектру ексиплексних молекул монойодиду кадмію, атомів кадмію, ксенону. Встановлено закономірності в змінах емісійних характеристик плазми в залежності від частоти слідування імпульсів накачки, компонентного і кількісного складів сумішей. Дані досліджень представляють інтерес для створення газорозрядного джерела, який випромінює одночасно у фіолетовому, зеленому, червоному і інфрачервоному спектральних діапазонах. Приведены результаты исследования спектральных, интегральных и ресурсных характеристик излучения газоразрядной плазмы на многокомпонентных смесях (дийодид кадмия с гелием и малыми добавками ксенона). Создание газоразрядной плазмы и возбуждение компонент рабочей смеси осуществлялось импульсно-периодическим (частота следования импульсов 18…20 кГц, длительность импульсов ~ 150 нс) барьерным разрядом. Выявлено излучение в видимой области спектра эксиплексных молекул монойодида кадмия, атомов кадмия, ксенона. Установлены закономерности в изменениях эмиссионных характеристик плазмы в зависимости от частоты следования импульсов накачки, компонентного и количественного составов смесей. Данные исследований представляют интерес для создания газоразрядного источника, который излучает одновременно в фиолетовом, зеленом, красном и инфракрасном спектральных диапазонах.